An Influential Technological Assistance: Consulting English Monolingual Dictionary Application in Evaluating Student’s English Writing - Muarfian Suryanudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2020)
This research was aimed to describe English Monolingual Dictionary Application, time to consult it, reasons to consult, and the advantages of consulting it in evaluating student’s English writing.The method of this study used descriptive qualitative and two kinds of instruments, namely interview, and documentation. There were three teachers being interviewed. This research resulted that they consulted Oxford Advance Learner’s Dictionary (OALD) 9th edition and Longman Dictionary of Contemporary English (LDOCE) 6th edition available on their own mobile phones. The teachers agreed that they must have consulted their English Monolingual Dictionary Application every time they found unfamiliar words during teaching academic writing especially during evaluating student’s writing. They consulted their English Monolingual Dictionary Application in view of some factors; namely, to confirm meaning, to check spelling, to check the examples of sentences, to check word classes, meaning, and to know whether the words used were grammatically applied well or not and to find synonym for paraphrase After analyzing the finding, the researcher gives some suggestions to the writing teachers, the English teacher, and reader. For the English writing teachers, they are expected to be able to consult English Monolingual Dictionary Application because this research showed that English Monolingual Dictionary Application provided so much help to support teaching in the class especially when evaluating student’s writing product.